Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Marta Rodríguez, descolonizando la representación documental latinoamericana - Moreno, Pedro Pablo Gómez (Estudios Artísticos, 2017)
En esta conversación entre la cineasta documental Marta Rodríguez y Pedro Pablo Gómez, antes que hacer un recorrido cronológico por el trabajo la artista, se abordan problemas tranversales que están presentes a lo largo de su obra: el cine documental como modo de representación; la construcción de una metodología del cine documental latinoamericano; el carácter decolonial de la obra de Rodríguez y su compromiso indeclinable durante más de cuatro décadas de acompañar las luchas de campesinos, indígenas y afrodescendientes, entre otros. Y es en este abordaje donde Marta Rodríguez, haciendo uso de una memoria extraordinaria, puede tejer un relato en el que se destaca la ética de la artista y su compromiso indeclinable de denuncia de las injusticias sociales, utilizando las tecnologías del cine, no para hablar por las víctimas, sino para hacer escuchar sus voces y mantener vivas sus imágenes; unas imágenes que interpelan el discurso colonial mediante el cual se ha tejido nuestro relato de nación. Dans cette conversation entre la cinéaste documentaire Marta Rodríguez et Pedro Pablo Gómez, avant d'entreprendre une tournée chronologique de l'œuvre de l'artiste, nous traitons les problèmes transversaux présents tout au long de son travail : le cinéma documentaire comme mode de représentation ; la construction d'une méthodologie du documentaire latino-américain; la nature décoloniale de l'œuvre de Rodríguez et son engagement pendant plus de quatre décennies pour accompagner les luttes des paysans, des indigènes et des Afro-descendants, entre autres. Et c'est dans cette approche que Marta Rodríguez, avec une mémoire extraordinaire, peut tisser une histoire qui souligne l'éthique de l'artiste et son engagement indécelable à dénoncer les injustices sociales, en utilisant les technologies du cinéma –pour ne pas parler en lieu des victimes, mais pour faire entendre leur voix et garder leurs images vivantes. Des images qui contestent le discours colonial par lequel notre récit de nation a été tissé.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créatrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Género, representación y nuevas tecnologías: mujeres y video en México - Pech, Cynthia (Revista mexicana de ciencias políticas y sociales, 2006)
En este artículo, se aborda la temática del video como tecnología de género. El video es el medio de creación artística que algunas mujeres están utilizando para crear lo que se puede llamar imá genes en femenino. Se hace un acercamiento al discurso feminista y los presupuestos teóricos que se han tomado para el análisis del discurso videográfico de las mujeres. Se presenta un breve análisis de los trabajos de las videastas Pola Weiss y Pilar Rodríguez.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Genre et sexualité; 2-Humanités numériques; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créatrice; _Nettoyé